Clinical and epidemiological teaching of dengue through simulated practice - João Henrique de Morais Ribeiro; Eloá Otrenti; Renata Ferreira Takahashi; Lúcia Yasuko Izumi Nichiata; Maria Clara Padoveze; Érica Gomes Pereira; Sebastião Silveira Nunes Júnior; Anna Luiza de Fátima Pinho Lins Gryschek; Suely Itsuko Ciosak
ABSTRACT Objective: to describe the experience of clinical teaching on dengue and the practice of epidemiological surveillance using problematization methodology. Method: report of experience on educational activity with undergraduate nursing students, held in March 2016, at a public university in the city of São Paulo, conceived in four stages: dialogic lecture, active search of Aedes aegypti, case study and simulation of nursing consultation to individuals with dengue. Results: The activity allowed to retrieve previous knowledge about the disease, respond to exercises that addressed different clinical situations and epidemiological surveillance, including in situ evaluation of possible mosquito outbreaks, and discuss the need to expand prevention and health of the individual and the community, the impact of the media in the dissemination of cases and the coping difficulties experienced in the different levels of attention. Conclusion: the methodology adopted enabled qualified training of students to cope with dengue.